Techno-Concepts for the Cultural Field: n-Dimensional Space and Its Conceptual Constellation - Rodríguez-Ortega, Nuria (My University, 2022)
Abstract This paper advocates an epistemological turn in the field of digital art history and cultural heritage studies. This epistemological turn is understood as the elaboration of a new (or renewed) epistemic apparatus that allows us to understand and interpret cultural phenomena from the perspective of a different order of thought. This epistemological labor is conceived of as an «epistemological technical practice», which means integrating epistemological reflection and production into technical making and design. Within this framework of discussion, this paper introduces the idea of a techno-concept, which is defined as a co-production between the machine rationale and the human thought/imagination. As particular cases, this paper argues that the mathematical concepts of n-dimensional, vector and latent spaces constitute examples of techno-concepts that can be reappropriated and reworked for cultural analysis and interpretation. This paper offers a preliminary inquiry, in which certain epistemological propositions are exposed as open gates for further discussions.
Keywords: Humanidades - Nuevas tecnologías; Digital humanities; Digital art history; Artificial intelligence; Techno-concepts; Vector space; N-dimensional space; Latent space